Absence of an effect of T89 on the steady‐state pharmacokinetics and pharmacodynamics of warfarin in healthy volunteers. (16th November 2013) - Wang, Ping; Sun, He; Yang, Liu; Li, Ling‐Yan; Hao, Jing; Ruff, Dennis; Guo, Zhi‐Xin
Abstract This open‐label, multi‐dose, single‐center, sequential, inpatient study evaluated the effects of a two herb combination drug (T89, Danshen plus Sanqi) on the steady‐state pharmacodynamics (PD) and pharmacokinetics (PK) of warfarin in 24 healthy volunteers. Twenty‐three subjects attained a stable international normalized ratio (INR) by taking warfarin alone prior to 1‐week of added‐on use of T89. INR was not increased after the addition of T89 for 7 days (P > .05). The 90% confidence interval (CI) of the geometric mean ratio for maximum plasma concentrations (Cmax) and area under curve (AUClast) of both R‐ and S‐warfarin when warfarin was administered with or without T89 was within the 0.80 to 1.25 equivalence ratio. These results indicate that T89 has no effect on the steady‐state PD and PK of warfarin. Warfarin and T89 dose adjustments are not required when these two drugs are co‐administrated in clinical practice.